Mesoporous Polydopamine Nanoparticles Attenuate Morphine Tolerance in Neuropathic Pain Rats by Inhibition of Oxidative Stress and Restoration of the Endogenous Antioxidant System - Yaswanth Kuthati; Prabhakar Busa; Srikrishna Tummala; Vaikar Navakanth Rao; Venkata Naga Goutham Davuluri; Yen-Peng Ho; Chih-Shung Wong (MDPI AG, 2021)
Oxidative stress resulting from reactive oxygen species (ROS) is known to play a key role in numerous neurological disorders, including neuropathic pain. Morphine is one of the commonly used opioids for pain management. However, long-term administration of morphine results in morphine antinociceptive tolerance (MAT) through elevation of ROS and suppression of natural antioxidant defense mechanisms. Recently, mesoporous polydopamine (MPDA) nanoparticles (NPS) have been known to possess strong antioxidant properties. We speculated that morphine delivery through an antioxidant nanocarrier might be a reasonable strategy to alleviate MAT. MPDAs showed a high drug loading efficiency of ∼50%, which was much higher than conventional NPS. Spectral and in vitro studies suggest a superior ROS scavenging ability of NPS. Results from a rat neuropathic pain model demonstrate that MPDA-loaded morphine (MPDA@Mor) is efficient in minimizing MAT with prolonged analgesic effect and suppression of pro-inflammatory cytokines. Additionally, serum levels of liver enzymes and levels of endogenous antioxidants were measured in the liver. Treatment with free morphine resulted in elevated levels of liver enzymes and significantly lowered the activities of endogenous antioxidant enzymes in comparison with the control and MPDA@Mor-treated group. Histopathological examination of the liver revealed that MPDA@Mor can significantly reduce the hepatotoxic effects of morphine. Taken together, our current work will provide an important insight into the development of safe and effective nano-antioxidant platforms for neuropathic pain management.